A study on the relationship between economic growth, inflation rate and labor force towards growth of small medium enterprise in Malaysia / Susilawati Maarof - Maarof, Susilawati (2006)
The purpose of this study is to determine the relationship between GDP, inflation and labor force within 31 periods starting from the year 1975 to 2005. The scope of this study is before and after establishment of SMEs. SMEs in Malaysia existed a long time ago but it was established and encouraged by the government in 1996. The data collection were based on yearly basis, apart from that, secondary data were also used. From the result, only GDP and labor force have significant relationships with the growth of SME, while inflation are not significant with the growth of SMEs. Thus, labor force is the most effective variable for growth of SMEs, although it has a negative relationship with growth of SMEs. Since the researcher had identified the most effective variables, it is recommended for BNM, SMIDEC and entrepreneurs to take GDP as a consideration when making decisions regarding to the growth of SMEs.